Service of Trading Business License (SIUP) through Online Single Submission (OSS) System at the Department of Investment and One Door Integrated Services (DPMPTSP) Gorontalo Regency - Sakbir Sakbir; Sukiman Idrus (Journal of Management and Administration Provision, 2021)
This study aims to determine the service of trading business permits through the Online Single Submission (OSS) system at the Investment Service and One Stop Services, Gorontalo District. The focus in this research is socialization, internet networking, and human resource capabilities. The research method uses a descriptive qualitative approach. The results of the study concluded that the socialization of Trade Business License services through the Online Single Submission (OSS) system has been carried out but has not been optimal because the socialization process is not followed up with assistance to business actors so that there are still many business actors, especially business actors in the MSME cluster who cannot operate the system. OSS. The internet network for Trading Business License services through the Online Single Submission (OSS) system is inadequate. This can be seen from the registration process or operation of the Online Single Submission (OSS) system which is considered complicated and has to be done repeatedly due to frequent network problems. The ability of officers in the service of Trading Business Permits through the Online Single Submission (OSS) system is good enough but not evenly distributed. This can be seen from the licensing service through the Online Single Submission (OSS) system which can only be operated by certain officers.